2014
DOI: 10.15517/rbt.v63i2.15178
|View full text |Cite
|
Sign up to set email alerts
|

Inversión reproductiva de Aratus pisonii (Decapoda: Sesarmidae): diferencias entre hábitats y análisis de rutas

Abstract: Reproductive investment of Aratus pisonii (Decapoda: Sesarmidae): differences among habitats and path analysis. Aratus pisonii is an abundant Neotropical mangrove crab that forages on fresh leaf tissue in the canopy and lives in a wide spectrum of habitats. It presents great plasticity in some aspects of its life history becoming an excellent subject for comparative studies. The purpose of this study was to investigate possible reproductive variations among populations of this crab in mangroves with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Recent studies confirm that the variety of resources consumed by A. pisonii is closely related to the structural development of the mangroves where they live (López and Conde 2013). Moreover, it has been found that the reproductive performance of this species responds to a gradient of structural complexity of the mangroves, and that fertility and the weight of the egg mass are correlated equally with the size of the crab, as well as with the environmental variables (salinity and structural development of the mangrove) (López-Sánchez and Quintero-Torres 2015).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent studies confirm that the variety of resources consumed by A. pisonii is closely related to the structural development of the mangroves where they live (López and Conde 2013). Moreover, it has been found that the reproductive performance of this species responds to a gradient of structural complexity of the mangroves, and that fertility and the weight of the egg mass are correlated equally with the size of the crab, as well as with the environmental variables (salinity and structural development of the mangrove) (López-Sánchez and Quintero-Torres 2015).…”
Section: Introductionmentioning
confidence: 87%
“…1), while in Paraguaná Peninsula, where rainfall is the only source of freshwater for the mangroves, there is only a short rainy period that usually last from October to November, in a predominantly dry climate with a long period of drought (Conde 1990); the rainfall is the only source of freshwater for the mangroves of the Paraguaná Peninsula. For more details about this study area, see López et al (2011) and López-Sánchez and Quintero-Torres (2015).…”
Section: Study Areamentioning
confidence: 99%